Dampak Pekerja Wanita di Perusahaan Mitra Sawit Jambi (MSJ) dalam Melaksanakan Hak dan Kewajiban terhadap Suami di Tinjau dari Aspek Hukum Keluarga Islam - Andesma Andesma; Ramlah Ramlah; Hermanto Harun (STIKes Ibnu Sina Ajibarang, 2025)
This research was motivated by a woman who worked in a company as a laborer who worked on an oil palm plantation. The research approach or methodology used in this research is the sociological juridical approach to interpreting law. The role of a woman apart from being a wife, a housewife plus being a worker should still have to carry out the rights and obligations as a wife even though the concepts in marriage are such that or in other words the goals of marriage are not achieved, Positive impact on household harmony for female workers: Women can live a decent life without having to experience pressure and dependence from their husbands; Can support their families, especially their children who have various needs; Can buy life's necessities or be financially independent to meet life's needs. everyday life; Happier because you meet co-workers who can joke with each other; Have a strong mentality, and will not panic when faced again with problems at home that have occurred; Increased self-confidence, because they feel more appreciated and recognized in the family and society. Meanwhile, negative impacts on household harmony for female workers: Lack of attention to husbands and children because they are busy with their work; Prioritizing work rather than providing rights and responsibilities as a wife and housewife. Lack of good communication with partners; Because they have their own income, they forget that the wife is the responsibility of husband Royal use of moneyRights and obligations aspect of Islamic family law There are two kinds of rights of a wife towards her husband, namely: material rights or economic rights to survive and non-economic rights such as the right to be applied fairly and not to be hurt, etc, apart from that, the right to love, respect, and be loyal to provide physical and spiritual assistance to both of them.